Doktrin Gereja (Ekklesiologi): Sebuah Kajian Literatur - Dina Radina Singal; Eny Emelia Hewuni; Eka Andika Saputra; Sarmauli (LANCAH: Jurnal Inovasi dan Tren, 2025)
This article discusses how church doctrine relates to the church, where the church, as the body of Christ, is inseparable from the fundamental teachings of its faith and confession. Doctrine is a crucial foundation that supports church life. In the New Testament, the word ekklesia refers to "out of the world," so the Church is seen as a gathering of chosen people called out from society. Church doctrine in history has two eras: the pre-Reformation era, consisting of the Church Fathers and the Middle Ages; and the post-Reformation era, consisting of the Reformation period and the eighteenth century. Church membership, according to church doctrine, is a combination of the inner aspect (faith) and the outer aspect (action). The requirements for membership according to church doctrine are the confession of faith, reception of the sacraments, and living under leadership.